What do we need to know to enhance treatment for multimorbid older patients?: results from the PACT study - Wild, Beate; Wurmbach, Viktoria; Böhlen, Friederike; Kusch, Marcel; Paul, Cinara; Friederich, Hans-Christoph; Hartmann, Mechthild; Slaets, J.; Seidling, Hanna (Aging & mental health, 2025)
OBJECTIVES: The aim of the PACT (Prioritization by pArticipation) study was to evaluate the 'Life and Vitality Assessment' (LAVA) in terms of visualizing and exploiting priorities, resources, and problem areas of elderly people. - METHOD: In total, n = 164 older persons (mean age: 68.6, 51.8% females) with multimorbid conditions were included. All patients completed the LAVA, additional questionnaires, and the INTERMED for the Elderly interview. The LAVA is a non-normative approach, applied in two steps: First, participants assign 25 aspects of life to three groups (not important, important, most important). Second, they rate their current satisfaction with the most important aspects on a scale from 1 to 10. - RESULTS: The majority of patients indicated that family (84.1%), mental health (84.8%), physical health (78.7%), and independent decision making (76.2%) were very important aspects of their life, mostly considered as resources. Variables related to negative well-being in older age-such as sleep quality and pain-were mostly considered as problem area. There was a high variability across patients regarding the number of resources and problem areas. - CONCLUSION: The LAVA provides important information on resources and problem areas, which might be helpful to improve quality of life for multimorbid patients by considering their resources for treatment planning.